2012
DOI: 10.1002/j.2205-0140.2012.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasound diagnosis of deep endometriosis: importance of the examiner's expertise and lesion size

Abstract: Objectives: To evaluate the accuracy of transvaginal sonography (TVS) in the diagnosis of deep infiltrating endometriosis (DIE) of the posterior compartment (rectovaginal septum, uterosacral ligaments, rectosigmoid colon, vagina) when undertaken by physicians of varying experience and to investigate if size of the nodule is relevant in influencing diagnostic accuracy. Methods: 381 patients who were operated on between January 2007 and December 2010 for suspected pelvic endometriosis were prospectively recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…1 represents the selection of studies. Of the 45 ( Fedele et al , 1998 ; Dessole et al , 2003 ; Delpy et al , 2005 ; Takeuchi et al , 2005 ; Bahr et al , 2006 ; Abrao et al , 2007 ; Biscaldi et al , 2007 ; Guerriero et al , 2007 ; Griffiths et al , 2008 ; Guerriero et al , 2008 ; Ribeiro et al , 2008 ; Valenzano Menada et al , 2008 ; Bazot et al , 2009 ; Hottat et al , 2009 ; Hudelist et al , 2009 ; Piketty et al , 2009 ; Bergamini et al , 2010 ; Chassang et al , 2010 ; Faccioli et al , 2010 ; Goncalves et al , 2010 ; Grasso et al , 2010 ; Pascual et al , 2010 ; Ferrero et al , 2011 ; Hudelist et al , 2011 ; Fiaschetti et al , 2012 ; Savelli et al , 2012 ; Bazot et al , 2013 ; Holland et al , 2013 ; Hudelist et al , 2013 ; Manganaro et al , 2013 ; Stabile Ianora et al , 2013 ; Leon et al , 2014 ; Tammaa et al , 2015 ; Baggio et al , 2016 ; Menakaya et al , 2016 ; Ferrero et al , 2017 ; Guerriero et al , 2017 ; Jiang et al , 2017 ; Ros et al , 2017 ; Alborzi et al , 2018 ; Carfagna ...…”
Section: Resultsunclassified
“…1 represents the selection of studies. Of the 45 ( Fedele et al , 1998 ; Dessole et al , 2003 ; Delpy et al , 2005 ; Takeuchi et al , 2005 ; Bahr et al , 2006 ; Abrao et al , 2007 ; Biscaldi et al , 2007 ; Guerriero et al , 2007 ; Griffiths et al , 2008 ; Guerriero et al , 2008 ; Ribeiro et al , 2008 ; Valenzano Menada et al , 2008 ; Bazot et al , 2009 ; Hottat et al , 2009 ; Hudelist et al , 2009 ; Piketty et al , 2009 ; Bergamini et al , 2010 ; Chassang et al , 2010 ; Faccioli et al , 2010 ; Goncalves et al , 2010 ; Grasso et al , 2010 ; Pascual et al , 2010 ; Ferrero et al , 2011 ; Hudelist et al , 2011 ; Fiaschetti et al , 2012 ; Savelli et al , 2012 ; Bazot et al , 2013 ; Holland et al , 2013 ; Hudelist et al , 2013 ; Manganaro et al , 2013 ; Stabile Ianora et al , 2013 ; Leon et al , 2014 ; Tammaa et al , 2015 ; Baggio et al , 2016 ; Menakaya et al , 2016 ; Ferrero et al , 2017 ; Guerriero et al , 2017 ; Jiang et al , 2017 ; Ros et al , 2017 ; Alborzi et al , 2018 ; Carfagna ...…”
Section: Resultsunclassified
“…The findings of the present study are in agreement with other investigators who showed that TVU was more effective than MRI in detecting recto‐vaginal endometriosis (TVU accuracy 97% vs MRI accuracy 71%). Savelli showed that TVU was an accurate method for detecting posterior DIE, but that this imaging technique strictly depended on the experience of the physician and the size of the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…9 Pre-operative ultrasounds performed by less experienced physicians (residents in training with 12-24 months of experience in gynaecological ultrasound) as compared to experienced physicians (gynaecologist specialised in gynaecologic ultrasound with more than 10 years experience) had a significantly reduced accuracy (80.9% vs 88.1%) and sensitivity (45.3% vs 77.1%). 9 Interestingly, it has been shown that sonographers are able to attain a skill level matched to that in expert centres within 38 scans if trained appropriately. 10 This adds further to the argument therefore that DIE-TVUS should become a part of standard ultrasound training or that only centres with a special interest and further training in endometriosis ultrasound should offer the service.…”
Section: Detailed Description Of Endometriosis With Ultrasound Ismentioning
confidence: 97%
“…However, TRUS is highly operator‐dependent and good diagnostic results may only be achieved by an adequately trained and experienced medical team 9 . Pre‐operative ultrasounds performed by less experienced physicians (residents in training with 12–24 months of experience in gynaecological ultrasound) as compared to experienced physicians (gynaecologist specialised in gynaecologic ultrasound with more than 10 years experience) had a significantly reduced accuracy (80.9% vs 88.1%) and sensitivity (45.3% vs 77.1%) 9 …”
Section: Introductionmentioning
confidence: 99%